O sítio arqueológico paleolítico do Salto do Boi (Cardina, Santa Comba, Vila Nova de Foz Côa) - Zilhão, João; Aubry, T.; Carvalho, A. F. de; Zambujo, G.; Almeida, F. (Trabalhos de Antropologia e Etnologia, 2020)
.